2013
DOI: 10.1146/annurev-genom-091212-153523
|View full text |Cite
|
Sign up to set email alerts
|

The RASopathies

Abstract: The RASopathies are a clinically defined group of medical genetic syndromes caused by germline mutations in genes that encode components or regulators of the Ras/mitogen-activated protein kinase (MAPK) pathway. These disorders include neurofibromatosis type 1, Noonan syndrome, Noonan syndrome with multiple lentigines, capillary malformation–arteriovenous malformation syndrome, Costello syndrome, cardio-facio-cutaneous syndrome, and Legius syndrome. Because of the common underlying Ras/MAPK pathway dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
765
0
25

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 767 publications
(799 citation statements)
references
References 68 publications
9
765
0
25
Order By: Relevance
“…This term was derived because each of the RASopathy syndromes is caused by gene mutations that result in dysregulated activity of "Ras" proteins or related molecules. Ras proteins are important for normal functioning of cells throughout the body (Rauen 2013). These proteins operate within a cellular signaling pathway known as the Ras mitogen-activated protein kinase (MAPK) signaling pathway.…”
Section: Molecular Genetic Basis Of Noonan Syndrome: a Brief Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This term was derived because each of the RASopathy syndromes is caused by gene mutations that result in dysregulated activity of "Ras" proteins or related molecules. Ras proteins are important for normal functioning of cells throughout the body (Rauen 2013). These proteins operate within a cellular signaling pathway known as the Ras mitogen-activated protein kinase (MAPK) signaling pathway.…”
Section: Molecular Genetic Basis Of Noonan Syndrome: a Brief Overviewmentioning
confidence: 99%
“…One variant causes a specific pattern of features that includes freckle-like skin markings ("lentigines") and is referred to as Noonan syndrome with multiple lentigines (NSML; formerly known as LEOPARD syndrome). This disorder is allelic to NS and caused by specific mutations in the same genes, specifically in PTPN11 or RAF1 (Rauen 2013). Another variant is caused by mutations in the SHOC2 gene and results in a phenotype that has been described by the term Noonan-like syndrome with loose anagen hair (NS/LAG) (Cordeddu et al 2009).…”
Section: Molecular Genetic Basis Of Noonan Syndrome: a Brief Overviewmentioning
confidence: 99%
“…2 NS is numbered among the RASopathies, a class of developmental disorders caused by germline mutations in genes encoding components or regulators of the RAS/MAPK pathway. Each RASopathy exhibits a specific clinical phenotype, but, given the involvement of a common mechanisms leading to the RAS/MAPK pathway dysregulation, they share many overlapping traits, including craniofacial dysmorphology, cardiac malformations, cutaneous and musculoskeletal abnormalities, neurocognitive impairment, hypotonia and an increased cancer risk 3 with the exception of Legius syndrome. 4 Compared with the other RASopathies, NS is characterized by a significant locus heterogeneity caused by the involvement of the mutated version of several RAS/MAPK pathway genes: protein tyrosine phosphatase, non-receptor type 11 (PTPN11), son of sevenless 1 (SOS1) and RAF1 in~60-70% of NS cases, and more rarely NRAS, KRAS, BRAF, MEK, SHOC2, CBL, RIT1 and RRAS genes.…”
Section: Introductionmentioning
confidence: 99%
“…Given its critical function, it is not surprising that deregulated Ras/ MAPK signaling, resulting from either genetic or environmental perturbations, can lead to developmental abnormalities. A large class of such abnormalities, known as RASopathies, is associated with activating germ-line mutations in many components of the Ras pathway (4). Estimated to affect 1/1,000 human births, these abnormalities are characterized by a broad spectrum of phenotypes, including cardiac defects, craniofacial dysmorphisms, and neurocognitive delays (4).…”
mentioning
confidence: 99%
“…A large class of such abnormalities, known as RASopathies, is associated with activating germ-line mutations in many components of the Ras pathway (4). Estimated to affect 1/1,000 human births, these abnormalities are characterized by a broad spectrum of phenotypes, including cardiac defects, craniofacial dysmorphisms, and neurocognitive delays (4). Although the origins of these phenotypes are still poorly understood, studies of model organisms show that many of the observed structural and functional defects can indeed be mimicked by targeted introduction of mutations found in RASopathies (5).…”
mentioning
confidence: 99%